Fiqih Dakwah Hadis Aisyah "Laula Anna Qawmaki ḥadītsu ‘ahdin bi kufr”: Kajian Implementasi Dalam Konteks Historis Dan Kontemporer: Kajian Implementasi dalam Konteks Historis dan Kontemporer - La Harisi, Isnain; Irawan, Deni; Majid, Abdul (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2025)
This study aims to examine the understanding of fiqih dakwah through the ḥadīth of ʿĀishah regarding the Prophet Muhammad’s (peace be upon him) decision to postpone the reconstruction of the Ka’bah. The background highlights the importance of wisdom (hikmah) in dakwah strategies that consider social and psychological contexts. Using a qualitative descriptive-analytical method based on library research, this study relies on primary sources from authentic ḥadīth collections and their commentaries, supported by contemporary scholarly works. The findings indicate that the Prophet prioritized social harmony by postponing the reconstruction, thereby applying principles of wisdom, prioritization, and unity in dakwah. The novelty of this research lies in its contextual and interdisciplinary analysis that connects the hadith with modern communication theories in Islamic propagation. The implication emphasizes that adopting wisdom-based approaches remains essential for effective dakwah in today’s multicultural societies.